Ground-Based Polarimetric Remote Sensing of Dust Aerosol Properties in Chinese Deserts near Hexi Corridor. (18th August 2014) - Xu, Hua; Li, Zhengqiang; Li, Donghui; Li, Li; Chen, Xingfeng; Xie, Yisong; Li, Kaitao; Chen, Cheng; Zhang, Yuhuan
Abstract : One-year observation of dust aerosol properties near Hexi Corridor was obtained from polarimetric measurements by ground-based sunphotometer in the county of Minqin in northwestern China from March 2012 to February 2013. We observed an annual mean AOD of 0.22 ± 0.22 at 0.50 μ m and Ångström exponents of 0.1–1.0 fitting a bimode normal distribution centered at 0.18 and 0.50, respectively. The effective radii of fine (0.13–0.17 μ m) and coarse (2.49–3.49 μ m) modes were found stable at all seasons together with the appearance of a third mode of particle radius at 0.4–1.0 μ m when AOD was larger than 0.6. It is noticeable that the real (1.5–1.7) and imaginary (0.0005 to 0.09) parts of complex refractive indices were higher than other studies performed in other desert regions of China, while single scattering albedo was relatively lower ( 0.84–0.89) at wavelengths of 0.44, 0.67, 0.87, and 1.02 μ m. This is partially due to calcite or hematite in the soil in Minqin or the influence of anthropogenic aerosols containing carbon. Moreover, from our novel polarimetric measurement, the scattering phase function (F 11 ) and degree of linear polarization for incident unpolarized light (- F 12 / F 11 ) of dust aerosols were also obtained within this deserted area.